1986
DOI: 10.1002/art.1780290413
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of Escherichia coli on adjuvant‐induced arthritis in germ‐free rats

Abstract: Our previous finding, that germ‐free F344 rats develop severe adjuvant‐induced arthritis, whereas specific pathogen–free rats develop mild disease, prompted us to investigate the role of bacterial flora in promoting the development of this disease. Germ‐free rats given Escherichia coli experienced disease suppression. Germ‐free rats treated with 3 strains of Lactobacillus experienced an enhancement of the disease, although it was not significant. Germ‐free rats treated with a combination of E coli and lactobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
36
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 26 publications
7
36
1
Order By: Relevance
“…Our findings are concordant with those described for adjuvant arthritis [21,22], a model with a pattern of susceptibility which is similar to that observed in SCW arthritis, Monoassociation of GF F344 rats with Gram-negative Escherichia coli resulted in resistance which equalled that in CV F344 rats whereas monoassociation with Gram-positive Lactobacillus casei did not really affect susceptibility, A combination of both bacteria suppressed susceptibility to a similar extent as E. coli alone. This suggests that Gram-negative bacterium-specific compounds, e.g, lipopolysaccharide (LPS; a known immunomodulator [23,24]), are responsible for decreased susceptibility.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are concordant with those described for adjuvant arthritis [21,22], a model with a pattern of susceptibility which is similar to that observed in SCW arthritis, Monoassociation of GF F344 rats with Gram-negative Escherichia coli resulted in resistance which equalled that in CV F344 rats whereas monoassociation with Gram-positive Lactobacillus casei did not really affect susceptibility, A combination of both bacteria suppressed susceptibility to a similar extent as E. coli alone. This suggests that Gram-negative bacterium-specific compounds, e.g, lipopolysaccharide (LPS; a known immunomodulator [23,24]), are responsible for decreased susceptibility.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, arthritis and severe inflammation can be induced in otherwise SCW arthritis-resistant F344/N rats, by interruption of the HPA axis at its effector end point, with the glucocorticoid receptor antagonist RU 486 (9). Taken together, these data indicate that LEW/N rats' pituitary and adrenal hyporesponsiveness to inflammatory and other stress mediators is a major factor contributing to their susceptibility to SCW arthritis, and possibly to other experimental inflammatory diseases (10)(11)(12)(13)(14)(15)(16)(17). This model is consistent with evidence that inflammatory-mediator activation of glucocorticoid secretion is one mechanism by which the immune response is appropriately regulated and restrained (18)(19)(20)(21).…”
mentioning
confidence: 68%
“…Literature data show that the exposure of mice/rats to certain bacteria can actually induce protection from, rather than development of a disease. It has been shown that E. coli can render germ-free rats resistant to subsequently induced AA [23]. Also, accumulating evidence suggests that resistance to AA was due to the protective effect of antibodies specifi c for some Hsps.…”
Section: Discussionmentioning
confidence: 99%